Dampak penggunaan teknologi dalam proses pembelajaran terhadap perkembangan kognitif anak usia dini - Shobikha, Maula Mima (Maliki Interdisciplinary Journal, 2025)
This research aims to describe the use of technology in early childhood learning, as well as the impact and ways to anticipate in preventing bad events that can occur due to lack of supervision from educators and parents. The research method used is literature study. After data collection, data analysis and conclusions are drawn. The results of the research can be concluded that technology can influence the cognitive development of early childhood, both in terms of creativity and memory which develops with technology. Unfortunately technology also has a negative impact on young children in that their health is threatened and has a negative impact on their social interactions. To anticipate all of this, parents and educators play a full role in guiding and supervising students. The use of technology in early childhood learning has a complex impact on their cognitive development. Although it can increase the stimulation of creativity and memory, the use of technology can also reduce children's social interactions and social skills, and has the potential to cause health problems due to lack of physical activity. Therefore, the integration of technology in the formal early childhood curriculum requires the teacher's role as an important facilitator and supervisor. It is also necessary to anticipate negative impacts by providing limits on the use of electronic devices, choosing safe content according to the child's age, monitoring the use of gadgets, balancing physical activity, and providing clear rules. A holistic approach that considers the benefits and risks of using technology in early childhood learning is crucial in ensuring children's optimal development in the future.